Edukasi Kesiapsiagaan Banjir Berbasis Sekolah bagi Siswa SMP Negeri 8 Bandar Lampung : Edukasi Kesiapsiagaan Banjir Berbasis Sekolah bagi Siswa SMP Negeri 8 Bandar Lampung - Munawaroh, Kholifatul; Yolanda Natsya; Meitha Agnes; Arrizqi Ziyadi; M. Asyaril Fajri; Tammia (Nemui Nyimah, 2025)
The community service activity aims to enhance flood preparedness and disaster literacy among students of SMP Negeri 8 Bandar Lampung through school-based education. Bandar Lampung City is an urban area with a relatively high level of flood vulnerability due to high rainfall intensity, population density, and inadequate drainage systems, which often cause inundation in the school environment during the rainy season. The activity was implemented through three main stages, namely situation analysis, educational socialization, and evaluation. The educational sessions were delivered using interactive presentations supported by visual media and educational videos, emphasizing the relationship between human behavior, environmental conditions, and flood risk. Evaluation was conducted using pre-test and post-test methods to measure improvements in students’ understanding. The results showed an increase in the average score from 77.58 in the pre-test to 91.37 in the post-test, with an N-Gain value of 66.81%, which falls into the effective category. These findings indicate that school-based flood preparedness education is effective in improving students’ knowledge, awareness, and environmentally responsible attitudes, and has the potential to support the development of disaster-resilient schools as well as flood risk reduction in both school and community environments.